Pengembangan Sistem Informasi Potensi Wilayah untuk Meningkatkan Perencanaan dan Pengelolaan Sumber Daya Daerah - Salfitri, Eka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This study focuses on the development and implementation of a Regional Potential Information System to enhance planning and resource management at the local level. The system aims to provide a comprehensive database of regional resources, including natural, economic, and social potentials, to support data-driven decision-making processes. Key features of the system include geospatial mapping, real-time data entry, resource categorization, and advanced analytics. By integrating GIS (Geographic Information Systems) and data visualization tools, the system enables stakeholders to identify and analyze the potential of various regions effectively. The research discusses the design, development, and deployment phases of the system, including technology selection, system architecture, and user interface considerations. The system is evaluated based on its impact on operational efficiency, accuracy of resource data, and user satisfaction. The results indicate that the implementation of the Regional Potential Information System leads to significant improvements in regional planning, resource allocation, and economic development. The paper also addresses the challenges encountered during the development and deployment phases, along with the solutions implemented to ensure successful integration and user adoption.